Lawi Ayam: Aesthetic experience and design-user system assessment of a Malay weapon artefact / Siti Mastura Md Ishak - Siti Mastura, Md Ishak (2017)
There is a need of Malay cultural product knowledge preservation for establishing the product design development in the new culture environment. Although many researches on Malay cultural artefacts in Malaysia, none of these documents has extensive information on sustainable user aesthetic experience knowledge. In fact, much documentation lingers on certain popular artefacts that typically known in Malay cultural design environment. Consequently, narrow understanding in local designers on Malay applied artefact due no rigorous research and limited documentation employing the design and the human science in user experience. This research shows that this knowledge comprehension can be expanded to higher level in both contexts of tangible and intangible for a new paradigm of Malay cultural product design. The purpose of this study is to systematize design-user interrelationship through aesthetic experience assessment on Malay Lawi Ayam (LA) artefact as a case study for establishing the Malay cultural product design knowledge. This study employed literature review and analytical observation on Malay Lawi Ayam weapon to document the characteristic of physical design and intangible knowledge for syntactic analysis. Then, this study conducted full participant observation and semi-structured interview to comprehend the aesthetic experience (AE) of the weapon user through pragmatic analysis and artefact usability evaluation. Finally, the study further undertook eye tracking test to investigate the eye behavioural responses and cognitive feedback in user pre-existent AE experience towards Malay Lawi Ayam design evaluation to amalgamate the knowledge between the artefact context (syntactic dimension) and the user context (pragmatic dimension). Drawing on Petersen’s methodology (2004) and Locher’s approach (2010) in relation to aesthetic interaction, the findings from the data analysis would include the; 1) design characteristic (physical and non-physical) and artefact terminology as factor that affects artefact effectiveness, 2) pragmatic knowledge and artefact usability of Malay Lawi Ayam user to understand the artefact usage through the body movement efficiency, and 3) cognitive knowledge from eye tracking evaluation to support the understanding of users’ eye behaviour on artefact design preference. These result expected to be a pioneer approach for Malay cultural product (MCD) knowledge preservation to assist the development of design in a new environment purposes. This research will present the literature on Malay Lawi Ayam, Aesthetic Experience, and design-user interaction. Then, the research methodology describes a comprehensive data acquisition strategy before presenting the expected results. This study contributes in; 1) Artefact classification knowledge of Malay Lawi Ayam from the comprehension on design characteristic, terminology and intangible knowledge (design philosophy), 2) Aesthetic experience knowledge through the understanding of artefact typology of Malay Lawi Ayam and user physical behaviour (movement) by integrating the syntactic findings into the pragmatic analysis, and 3) the development of a design-user interrelationship system (DUs) with the implementation of Malay design knowledge from artefact classification and artefact user’s aesthetic experience using technology of eye movement test. Findings from this study benefits the product designers, behavioural researchers and ethnographers for the field of design and the cultural artefact research relating to design-driven and cognitive-driven to provide holistic understanding for Malay cultural design (MCD).